TINJAUAN KRITIS: METHODS FOR INVESTIGATING LOCALS’ PERCEPTIONS OF A CULTURAL HERITAGE PRODUCT FOR TOURISM LESSONS FROM BOTSWANA-SUSAN KEITUMETSE - Ari Widyati Purwantiasning (Universitas Muhammadiyah Jakarta, 2019)
ABSTRAK. Dalam sebuah penelitian kualitatif, dikenal banyak sekali metode pendekatannya, salah satu metode pendekatan dalam penelitian kualitatif adalah pendekatan etnografi di mana di dalamnya menggunakan visualisasi. Tulisan ini merupakan sebuah ulasan dan tinjauan mengenai bagaimana pendekatan etnografi dalam hal ini penggunakan metode visualisasi digunakan dalam menggali data-data dari masyarakat langsung. Tulisan Susan Keitumetse dengan judul “Methods for Investigating Local’s Perceptions of a Cultural Heritage Product for Tourism: Lessons from Botswana”, merupakan salah satu paparan dari penelitian yang dilakukan Susan Keitumetse dalam menggali informasi dari masyarakat dengan menggunakan pendekatan etnografi dengan visualisasi. Susan menggunakan pendekatan ini untuk menggali informasi seberapa jauh peran masyarakat dalam kegiatan pariwisata berbasis cultural heritage. Banyaknya kendala yang ditemui dalam penggalian data dengan menggunakan metode ini, tentunya justru dapat menjadi catatan penting bagi penelitian lainnya yang sejenis yang menggunakan pendekatan etnografi. Kata Kunci: Cagar Budaya, Botswana, Persepsi Masyarakat, Metode Investigasi ABSTRACT. In the qualitative research, there are many approach method; one of the approaches in qualitative research is an ethnography approach which uses visualization as a tool. This paper is a review of how an ethnography approach, particularly in using visualization method, is using to digging up information from local’s community directly. Paper of Susan Keitumetse titled “Methods for investigating Local’s Perception of a Cultural Heritage Product for Tourism: Lessons from Botswana,” is one of a discussion from research which has been done by her to digging up the information from the local community by using ethnography approach with visualization. Susan has used this approach to digging up how far the role of society in the activity of tourism based on cultural heritage. Many challenges have been met for sure in using this approach, but these challenges will become an essential note for the next another research which using this ethnography approach. Keywords: Cultural Heritage, Botswana, Local’s Perception, Methods for Investigating